ARCHITECTURAL DEVELOPMENT OF SUBLIME PORTE - Gundogan, Sabiha Akman (YILDIZ TECHNICAL UNIV, 2011)
The Babiali is the governmental center of the Ottoman Empire. Changes in ideology of the government during the middle of the seventeenth century lead to formation of The Babiali. Changes in ideology of the government are the beginning of development of the governmental architecture. Using grand vizier mansions as official buildings accelerated to formation of The Babiali.
Keywords: Ottoman government; Ottoman architecture; westernization; Engineering